Pengaruh Konseling Behavioral dengan Teknik Modeling Melalui Lesson Study terhadap Self Exhibition - Lastrini, Kadek; Tirka, I Wayan; Dantes, Nyoman (Jurnal Jurusan Bimbingan Konseling Undiksha, 2019)
The current study was aimed at analyzing the effect of Behaviour counseling with modeling technique Through Lesson Study to self-exhibition. The study was a quasi-experiment, with non-equivalent posts only control group design. Purposive sampling was used to select the subject of the study. 10 tenth grade students of SMKN 3 Singaraja were selected as the subjects of the study. Observation, interviews, diaries, and self-exhibition likert scale questionnaire were used as the methods of data collection. The data was analyzed descriptively and statically, using t-test. Based on the observed t-value (14,54) with the t-table of 6.39 on significant level of 0.05, it was concluded that the H1 was accepted. In conclusion, the result of the study confirmed the effect of behaviour counseling with modeling technique through Lesson StudyÂ  to improve studentsâ€™ self-exhibitionKeywords: Behaviour Counseling, Modeling, Self Exhibition.